PENGARUH KOMPOS TANDAN KOSONG KELAPA SAWIT (TKKS) DENGAN PUPUK KCL TERHADAP PERTUMBUHAN DAN HASIL TANAMAN BAWANG MERAH (Allium ascalonicum L.) PADA MEDIUM GAMBUT - Joko Prasetyo; Armaini Armaini; Murniati Murniati (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
Onion production which decreased in Riau province affected by the lack of interest and experience of farmers. Riau has extensive peatlands, efforts to increase the productivity of peat soil as crop production land can be done by combining the use of organic such as compost oil palm empty fruit bunches (EFB) and inorganic fertilizers such as manure KCl. This study aimed to determine the effect of the combination of composted manure TKKS with KCl and get a dose of compost TKKS combination with best KCl fertilizer which can improve the growth and yield of onion on the peat medium. The research was conducted in the House Kasa, the Experimental Farm of Agriculture Faculty, University of Riau, in November 2015 until February 2016. The research was conducted experimentall using on completely randomized design (CDR) with 4 treatments and 5 replications. The data were analyzed statistically by analysis of variance and tested further with Duncan's multiple range test at 5% level. The results showed that the administration of various doses of compost TKKS with KCl fertilizer can not increase the plant height parameters, number of tuber per hill and the circumference of the tuber however the good effects toward the tuber weight fresh and the tuber shelf weight per clump on onion crop. Giving compost TKKS with fertilizer KCl at a dose of 150 kg K2O / ha showed the best results because it can increase the tuber weight fresh and the tuber shelf weight per clump. Keywords: Allium ascalonicum L., Peat, TKKS compost, fertilizers KCl